Removal of Dissolved Organic Matter in Drinking Water Using Active Microorganisms (EM) - Yalçın, Zehra Gulten; Dağ, Mustafa; Aydoğmuş, Ercan (Osman SAĞDIÇ, 2022)
Conventional treatment methods are used in the treatment of drinking water to protect human and environmental health. These methods can be named aeration to increase the amount of oxygen, precipitation, chemical treatment, filtration, chlorination for disinfection. Besides, iron and manganese removal operations are performed in places where the hardness is very high depending on the geographical location, iron and manganese removal operations are performed in cases where the iron and manganese content is high. Drinking, and drinking water treatment technologies in Turkey are generally the same. The conventional methods used are briefly described as ventilation, coagulation, flocculation, precipitation, sand filtration, and chlorination. In recent years, it has been observed that in addition to these methods, ozone has been used for primary disinfection purposes, activated carbon adsorption for advanced purification purposes, reverse osmosis studies have been performed. Conventional treatment plants are usually built when there is the use of superficial water sources. In settlements where spring or well water is used in a certain area, the water is only available by the chlorination process. The purpose of drinking water treatment is to be clear, colorless, odorless, disease-causing organism-free, free of chemicals harmful to health, and suitable for domestic use. The treatment technologies used in drinking water treatment plants vary depending on the properties that are desired to be found in purified water, as well as the properties of raw water. Physical, chemical, and biological purification, which is one of the classical methods used in the purification process, may be insufficient in the face of dissolved organic matter. This encourages us to look for new methods of combating dissolved organic matter.

İçme sularının arıtılmasında insan ve çevre sağlığını korumak için geleneksel arıtma yöntemleri kullanılmaktadır. Bu yöntemler oksijen miktarını artırmak için havalandırma, çöktürme, kimyasal arıtma, filtrasyon, dezenfeksiyon için klorlama olarak adlandırılabilir. Ayrıca coğrafi konuma bağlı olarak sertliğin çok yüksek olduğu yerlerde demir ve mangan giderme işlemleri, demir ve mangan içeriğinin yüksek olduğu durumlarda ise demir ve mangan giderme işlemleri yapılmaktadır. Türkiye'de içme ve içme suyu arıtma teknolojileri genel olarak aynıdır. Kullanılan geleneksel yöntemler kısaca havalandırma, pıhtılaşma, flokülasyon, çökeltme, kum filtrasyonu ve klorlama olarak tanımlanmaktadır. Son yıllarda bu yöntemlere ek olarak birincil dezenfeksiyon amacıyla ozonun kullanıldığı, ileri saflaştırma amaçlı aktif karbon adsorpsiyonunun kullanıldığı, ters ozmoz çalışmalarının yapıldığı görülmektedir. Konvansiyonel arıtma tesisleri genellikle yüzeysel su kaynaklarının kullanıldığı durumlarda kurulur. Kaynak veya kuyu suyunun belirli bir bölgede kullanıldığı yerleşim yerlerinde, su sadece klorlama işlemi ile elde edilmektedir. İçme suyu arıtımının amacı; berrak, renksiz, kokusuz, hastalık yapıcı organizmalardan arınmış, sağlığa zararlı kimyasallardan arındırılmış ve ev içi kullanıma uygun olmasıdır. İçme suyu arıtma tesislerinde kullanılan arıtma teknolojileri, ham suyun özelliklerinin yanı sıra arıtılmış suda bulunması istenen özelliklere bağlı olarak değişiklik göstermektedir. Saflaştırma işleminde kullanılan klasik yöntemlerden biri olan fiziksel, kimyasal ve biyolojik saflaştırma, çözünmüş organik madde karşısında yetersiz kalabilmektedir. Bu, bizi çözünmüş organik maddelerle mücadele için yeni yöntemler aramaya teşvik ediyor.
Aktif Mikroorganizmalar (EM) Kullanılarak İçme Suyundaki Çözünmüş Organik Maddenin Uzaklaştırılması
Keywords: Engineering; Mühendislik